Solution-processable pyrite FeS(2) nanocrystals for the fabrication of heterojunction photodiodes with visible to NIR photodetection - Wang, Di-Yan (Advanced materials (Deerfield Beach, Fla.), 2012)
Copyright © 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.